A remarkable new species of Zoraptera, Zorotypus asymmetristernum sp. n., from Kenya (Insecta, Zoraptera, Zorotypidae) - Mashimo, Yuta; Matsumura, Yoko; Beutel, Rolf G.; Njoroge, Laban; Machida, Ryuichiro (Zootaxa, 2018)
A new species of order Zoraptera, Zorotypus asymmetristernum Mashimo, n. sp., is described from Kakamega, Kenya, with its major diagnostic features and characteristics of the egg described and illustrated. The new species represents the sixth zorapteran species from the Afrotropic ecozone. A brief discussion on vestigial eye spots of apteron individuals and a key to the species of the Afrotropic ecozone are provided.